2021
DOI: 10.3390/brainsci11010048
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Visual Magnocellular Event-Related Potentials in Developmental Dyslexia

Abstract: (1) Background—the magnocellular hypothesis proposes that impaired development of the visual timing systems in the brain that are mediated by magnocellular (M-) neurons is a major cause of dyslexia. Their function can now be assessed quite easily by analysing averaged visually evoked event-related potentials (VERPs) in the electroencephalogram (EEG). Such analysis might provide a useful, objective biomarker for diagnosing developmental dyslexia. (2) Methods—in adult dyslexics and normally reading controls, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…They measured visual evoked potentials in response to a moving checker board stimulus in 5 dyslexics and found that their latency was longer and amplitude smaller compared with 7 good readers. This result has been confirmed many times, in much larger samples and with more advanced technology ( Klistorner et al, 1997 ; Schulte-Körne and Bruder, 2010 ; Jednoróg et al, 2011 ; Stein, 2021 ) and the result is no longer seriously doubted, although whether the deficit is due to undersampling due to smaller and sparser retinal magnocells, longer integration times or increased local noise, is still debated ( Manning et al, 2019 ).…”
Section: Visual Event Related Potentialsmentioning
confidence: 87%
See 1 more Smart Citation
“…They measured visual evoked potentials in response to a moving checker board stimulus in 5 dyslexics and found that their latency was longer and amplitude smaller compared with 7 good readers. This result has been confirmed many times, in much larger samples and with more advanced technology ( Klistorner et al, 1997 ; Schulte-Körne and Bruder, 2010 ; Jednoróg et al, 2011 ; Stein, 2021 ) and the result is no longer seriously doubted, although whether the deficit is due to undersampling due to smaller and sparser retinal magnocells, longer integration times or increased local noise, is still debated ( Manning et al, 2019 ).…”
Section: Visual Event Related Potentialsmentioning
confidence: 87%
“…Thus M- cells give a larger response at the 2nd harmonic, whereas linear P cells do so mainly at the fundamental frequency. Hence typical readers give a larger cortical response at the second harmonic, but dyslexics do so at the fundamental frequency, and this phenomenon has been exploited by comparing the fundamental and 2nd harmonic peaks in steady state visual evoked potentials recorded from dyslexics as a simple test of their magnocellular sensitivity ( Stein, 2021 ).…”
Section: Retinamentioning
confidence: 99%
“…les izquierdas, que dificultan el control de los movimientos oculares, la búsqueda y enfoque visual, conservando la capacidad para discriminar el color de los estímulos visuales (Stein, 2021;Nguyen et al, 2021). Las características de la atención visual están relacionadas con una disfunción bilateral en los lóbulos parietales superiores, que involucra un proceso inadecuado en el rendimiento de tareas secuenciales de la atención (Valdois et al, 2019;Zhao, Liu, Liu & Huang, 2018a).…”
Section: Características De La Atención En El Teapzunclassified
“…N1, a prominent component related to auditory processing and attention, is reduced in response to brief stimuli presented at interstimulus intervals (ISIs) of 100-200 ms in poor readers, who perform worse in a temporal ordering task as compared to good readers (Nagarajan et al, 1999). In the visual domain, dyslexic participants show atypical ERP patterns in response to coherently moving dots (Schulte-Körne et al, 2004) as well as flickering checkerboards (Stein, 2021). Using an attentional-shifting task, Wijers et al (2005) reported that, whereas normal readers presented a positive frontal activity (around 350 ms) lateralized over the right hemisphere, dyslexic participants showed this effect over both hemispheres, suggesting a dysregulation of interhemispheric asymmetry.…”
Section: Introductionmentioning
confidence: 99%